2014
DOI: 10.1093/jpids/piu081
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Human Serum Albumin-Free MMR Vaccine in US Children Aged 12-15 Months

Abstract: BackgroundM-M-RTMII (MMRII; Merck & Co) is currently the only measles-mumps-rubella (MMR) vaccine licensed in the United States. Another licensed vaccine would reinforce MMR supply. This study assessed the immunogenicity of a candidate vaccine (PriorixTM, GlaxoSmithKline Vaccines [MMR-RIT]) when used as a first dose among eligible children in the United States.MethodsIn this exploratory Phase-2, multicenter, observer-blind study, 1220 healthy subjects aged 12–15 months were randomized (3:3:3:3) and received 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…However, the underlying mechanism of FDXACB1 leading to MSI remains unknown. Some reviews speculated that such gene may contribute to the MSI by interfering MMR and functionally involving with the PD‐1/PD‐1L pathways, validating our prediction.…”
Section: Discussionsupporting
confidence: 81%
“…However, the underlying mechanism of FDXACB1 leading to MSI remains unknown. Some reviews speculated that such gene may contribute to the MSI by interfering MMR and functionally involving with the PD‐1/PD‐1L pathways, validating our prediction.…”
Section: Discussionsupporting
confidence: 81%
“…It is reported that parotid gland swelling occurred in 0-1.8%, and that the incidence of symptoms related to aseptic meningitis was 0-0.1% following immunization with GSK-MMR containing RIT4385 in several clinical trials. 18,26,27 The actual incidence must be assessed in a post-marketing study; accordingly, no case of vaccineassociated aseptic meningitis was reported in a 2-year postmarketing study in Germany that involved 1,575,936 children who had received the GSK-MMR vaccine containing RIT4385. 27 There was no immediate reaction or serious ADR after vaccination with JVC-001, indicating that JVC-001 is safe and well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The initial phase II, randomized, observer-blind study was conducted between June 2009 and July 2010 at 48 centers in the USA and 3 centers in Puerto Rico (NCT00861744) 13 . In this study, we continued to follow children for 2 y post-primary vaccination.…”
Section: Methodsmentioning
confidence: 99%
“…Currently there is only one MMR vaccine licensed in the USA (M-M-R II; Merck, USA), and any interruption to this single supply line could be a public health risk 3 . Another MMR vaccine, Priorix™ (MMR-RIT [RIT strain 4385]; GSK, Belgium), is licensed in over 100 countries 13 and has been shown to be immunogenic and well-tolerated in trials conducted in the USA 13-15 . Furthermore, as the MMR-RIT vaccine, like the current formulation of the M-M-R II vaccine, is manufactured without Human Serum Albumin (HSA) in accordance with the European Medicines Agency (EMA) guidelines, the theoretical risk of microbial contamination is reduced compared with previous formulations of the M-M-R II vaccine 16,17 …”
Section: Introductionmentioning
confidence: 99%